(untitled) (Revista Brasileña de Terapia Comportamental y Cognitiva, 2019)
Creativity, or the generation of previously unobserved behavior, is a topic of interest to scientists and the general public alike. Researchers outside behavior analysis have focused on creativity as a trait of individuals. Behavior analysts, however, have focused on the variables that give rise to novel responses. Initial conceptual work examined specific environmental variables that may promote creativity. Subsequent conceptual work examined the role of the response class and the selective nature of reinforcement. As this conceptual work progressed, researchers began evaluating variables that affect response variability, a potentially critical component of variability. Most basic researchers, and some applied researchers, have focused on response sequences. Although this work has proven fruitful in understanding response variability as an operant dimension, these limited response classes have prevented a more robust understanding of variability and novelty. Following the development of the lag schedule, applied researchers began using lag schedules to increase complex behavior behavior such as responses to questions, social skills, and martial arts skills. This applied work has provided intriguing evidence that variability, and environmental influence of variability, is a key contributor to novel responding, thus bringing creativity well into our scientific understanding of behavior.